2019
DOI: 10.1002/ldr.3338
|View full text |Cite
|
Sign up to set email alerts
|

Remotely sensed albedo allows the identification of two ecosystem states along aridity gradients in Africa

Abstract: Empirical verification of multiple states in drylands is scarce, impeding the design of indicators to anticipate the onset of desertification. Remote sensing‐derived indicators of ecosystem states are gaining new ground due to the possibilities they bring to be applied inexpensively over large areas. Remotely sensed albedo has been often used to monitor drylands due to its close relationship with ecosystem status and climate. Here, we used a space‐for‐time‐substitution approach to evaluate whether albedo (aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
(126 reference statements)
0
7
0
Order By: Relevance
“…However, above the ending elevation, there were mainly alpine meadows and a few shrubs ( Figure 14). In addition, the albedo of the shrubs is higher than that of the alpine meadows but lower than that of the coniferous forests [76,86], and this may explain why the albedo states can show such a trend in Figure 12. Therefore, elevation is a key factor in the altitudinal structure of vegetation in mountainous ecosystems [29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, above the ending elevation, there were mainly alpine meadows and a few shrubs ( Figure 14). In addition, the albedo of the shrubs is higher than that of the alpine meadows but lower than that of the coniferous forests [76,86], and this may explain why the albedo states can show such a trend in Figure 12. Therefore, elevation is a key factor in the altitudinal structure of vegetation in mountainous ecosystems [29].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ecosystems can be regarded as composed of multiple state modes, and each mode tends to present the most similar one with the adjacent state. Thus, when different state variables vary abruptly and exhibit an area of coexistence along the environmental gradient, a critical transition may occur between these states [29,76]. Potential analysis is a technique, which is used to establish a link between environmental gradients and state variables.…”
Section: Potential Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Remotely sensed vegetation indices (VIs), such as the normalized difference vegetation index (NDVI), have been used to monitor ecosystem functioning in drylands worldwide at multiple scales, from local [20]- [22] to regional [23]- [25] and global [26], [27] scales. Remotely sensed albedo (defined as the ratio of upwelling to downwelling radiative flux at the surface) is another commonly used indicator to monitor dryland degradation due to its close relationship with land surface changes [28]- [32]. Zhao et al [26] found significant correlations between broadband albedo metrics and ecosystem multifunctionality (i.e., a proxy of the capacity of the ecosystem to provide multiple functions simultaneously) in global drylands.…”
Section: Introductionmentioning
confidence: 99%